Sipunculan Fauna in the Fethiye-Gφηek Specially Protected Area (Turkey, Eastern Mediterranean) - ACIK, S. (Mediterranean Marine Science, 2010)
This study deals with sipunculan species collected from 0 to 31 m depths at 83 stations in the Fethiye-Göçek Specially Protected Area (Turkey). A total of 7 species and 1397 individuals belonging to four families were encountered. Among the species, Nephasoma (Nephasoma) rimicola is new to the eastern Mediterranean fauna and 5 species are new to the marine fauna of the southern coast of Turkey. Phascolosoma (Phascolosoma) stephensoni has the highest dominance and frequency index values in the area. Aspidosiphon (Aspidosiphon) elegans and Apionsoma (Apionsoma) misakianum are alien species. Of the biotopes examined, Posidonia oceanica was characterized by the highest number of species (6 species). In the present study, brief descriptions of the species, and their distributional and ecological characteristics are given and discussed.